Hydrodynamic numerical investigation and sedimentation, a study cases in Lontar steam-electric power plant - Suciana Suciana; Alamsyah Kurniawan (Journal of Science and Applicative Technology, 2023)
The intake pump of the Lontar steam-electric power plant cannot operate optimally due to a drawdown in the forebay. The capacity of the conveying channel decreases, possibly caused by sedimentation at the intake mouth. So, an initial investigation is required using hydro-oceanographic and sedimentation numerical modeling in that area. Numerical modeling is conducted to simulate flow phenomena to obtain a model and measurement data for qualitative assessment. Hence, the flow condition in the study area is a mix of ocean current and circulating water pump discharge. Hydrodynamic modeling has been successfully conducted to assess their interaction in this zone properly by using open-source software called Delft3D Hydro-morphodynamic. This research uses primary data or field measurement data like bathymetry, sediment, and discharge data for input. Model calibration used tidal and current data. Based on the results of the numerical modeling, it is evident that sediment deposition occurs at the intake mouth area due to the suction of the circulating water pump unit, resulting in sediment being carried and deposited during high water levels and a slowing down of flow rate. Sedimentation issues can addressed through dredging, and for the long-term recommendation to install a breakwater to extend the dredging service life at the intake mouth.